EXPLORING THE MOBILE DEVICES AS A NEW FRONTIER FOR THE E-LEARNING IN INSTRUMENTATION AND MEASUREMENT - Cmuk, Drago; Grimaldi, Domenico; Rapuano, Sergio (International Journal of Computing, 2014)
The mobile-learning establishes a new frontier for the research of the e-learning in the electrical and electronic measurement and instrumentation. Indeed, the reduced functionalities of the mobile devices must be integrated with the typologies of the services delivered to the student. By referring to the Remote Didactic Laboratory Laboratorio Didattico Remoto – LA.DI.RE. “G. Savastano” the delivered services taken into account are: experiment visualization, experiment control, and experiment creation. In order to enable the user of the mobile device to view, control and create the experiment application, several software architectures have been considered. Finally, the description of the solution adopted is given in the framework of the LA.DI.RE. “G. Savastano”.